Tratamento térmico na manutenção da coloração de lichias - de Souza, Angela Vacaro de [UNESP]; Lopes Vieites, Rogério [UNESP]; Douglas, Seijum Kohatsu [UNESP]; Lima, Giuseppina Pace Pereira [UNESP] (My University, 2010)
The objective of the work was to evaluate the influence of the thermal treatment in the color of lychee fruits. The fruits were treated by 0; 5; 10; 15; 20 and 25 minutes of water immersion at 45°C, packaged in expanded polystyrene trays and film of polyvinyl chloride 0.020mm, stored in B.O.D. at 5°C and 90±5% of UR. The experimental delineation was in a completely randomized scheme, with 6 times of storage for the color and enzymatic analysis, until they reached the limit for the marketing for the analysis of the shelf-life, and the fruits were analyzed every 3 days, with 3 replications and 10 fruits in each experimental unity. The evaluated parameters were: visual analysis of the browning, color and specific activity of the polyphenol oxidase and the peroxidase. The treatments using 5 and 10 minutes of immersion showed the best results in maintaining the color of the fruits and in the reduction of the enzymatic activity.
Thermal treatment in lychee color maintenance
Keywords: Color; Enzymatic browning; Litchi chinensis